The Problem of Multiple Land Exchange Certificates in Gebyog Village, Mojogedang District: Problematika Sertipikat Ganda Tukar Menukar Tanah di Desa Gebyog Kecamatan Mojogedang - Rahmawati, Dhestika; Suhadi, Suhadi (Annual Review of Legal Studies, 2024)
Exchange of Village Treasury Land with Land Ownership Rights in Gebyog Village, Mojogedang District, Karanganyar Regency which occurred in 1977. The exchange that occurred in 1977 was only done verbally so there is no written evidence. This study aims to: (1) Find out the Process of Exchanging Village Treasury Land with Land Owned by Residents in Gebyog Village, Mojogedang District, Karanganyar Regency? (2) Find out the factors causing the emergence of two certificates, namely the right to use in the name of the Gebyog village government and the right to own in the name of an individual? This study uses an empirical legal research method, with a Qualitative approach. The types and sources of research data are Primary data, Secondary data, and Tertiary data. Primary data is obtained through interviews and observations, Secondary data is obtained through laws and regulations and literature studies, and Tertiary data through the Great Dictionary of the Indonesian Language. Data is analyzed descriptively qualitatively. The results of the study were (1) the exchange carried out by the Gebyog Village Government with the Gebyog Village community (the late Kasan Mulyadi, the late Muh Thulabi, and Marinah). The exchange occurred in 1977 and occurred verbally. The exchange occurred because residents complained to the Head of Gebyog Village that they wanted to have rice fields as their livelihood and the Gebyog Village Government also wanted to build an elementary school in Gebyog Village. (2) the existence of a double certificate on the Land Owned by Residents that was exchanged, two certificates were issued, namely when the land registration took place Kasan Mulyadi had died so that the one who registered it was Imam Ahmad. Intentionally or unintentionally, Imam Ahmad registered land that did not match the one he owned and in 1996 there was no plotting so it had not been mapped properly.